2016
DOI: 10.1088/0029-5515/56/7/076011
|View full text |Cite
|
Sign up to set email alerts
|

Rotational shear effects on edge harmonic oscillations in DIII-D quiescent H-mode discharges

Abstract: In the quiescent H-mode (QH-mode) regime, edge harmonic oscillations (EHO) play an important role in avoiding transient edge localized mode (ELM) power fluxes by providing benign and continuous edge particle transport. A detailed theoretical, experimental and modeling comparison has been made of low-n (n≤5) EHO in DIII-D QH-mode plasmas. The calculated linear eigenmode structure from the extended MHD code M3D-C1 matches closely the coherent EHO properties from external magnetics data and internal measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 49 publications
21
76
0
Order By: Relevance
“…Indeed intriguing similarities between such perturbations and EHOs are found: the structure of the radial eigenfunction (cf. (13)) resembles closely experimental measurements [5], the rotation frequency of the mode scales as nΩ * (with Ω * the value of toroidal rotation at the pedestal top) with the growth rate (and presumably the saturated non-linear state) being independent of the sign of Ω * . A further extension of this work will be to include X-point effects but this is beyond the scope of the present paper.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Indeed intriguing similarities between such perturbations and EHOs are found: the structure of the radial eigenfunction (cf. (13)) resembles closely experimental measurements [5], the rotation frequency of the mode scales as nΩ * (with Ω * the value of toroidal rotation at the pedestal top) with the growth rate (and presumably the saturated non-linear state) being independent of the sign of Ω * . A further extension of this work will be to include X-point effects but this is beyond the scope of the present paper.…”
Section: Discussionsupporting
confidence: 76%
“…Since experimental evidence (see e.g. [1,5]) and nonlinear simulations [15] dictate that low-n (especially n = 1) modes are dominant, we concentrate on the linear stability properties, and marginal stability conditions, for low-n ideal modes. Critical to the work is the inclusion of low magnetic shear and steep pressure gradients in the edge and the extension of magnetic perturbations across a vacuum region to a conducting wall.…”
Section: Introductionmentioning
confidence: 99%
“…A linear eigenmode analysis of the EHO-like low-n modes using M3D-C1 indicated that these modes were destabilized by rotation and/or rotation shear, independently of the rotation direction [16]. This is consistent with the earlier observations of EHOs [8] and supports the view that the EHOs are saturated low-n kink/peeling modes destabilized by edge E × B flow shear [4,9].…”
Section: E × B Flow Shear Drive Of the Linear Low-n Modes Of Eho In Tsupporting
confidence: 86%
“…Destabilization of the low-n modes was seen in recent MHD simulation using M3D-C1 [16] and BOUT++ [17] codes. A linear eigenmode analysis of the EHO-like low-n modes using M3D-C1 indicated that these modes were destabilized by rotation and/or rotation shear, independently of the rotation direction [16].…”
Section: E × B Flow Shear Drive Of the Linear Low-n Modes Of Eho In Tmentioning
confidence: 85%
See 1 more Smart Citation